Do Financial Decisions Enhance Firm Value? The Mediating Role of Performance in Indonesia Consumer Non-Cyclical Firms - Ana Dwi Setyaning; Maulida Nurul Innayah; Naelati Tubastuvi; Hengky Widhiandono (Owner : Riset dan Jurnal Akuntansi, 2026)
This study investigates the effects of investment decisions, capital structure, dividend policy, and institutional ownership on firm value, with firm performance as a mediating variable, in the consumer non-cyclical sector listed on the Indonesia Stock Exchange. The sample comprises 38 firms with 150 panel data observations for the 2020-2024 period, selected using purposive sampling. Data analysis employed panel regression models fixed effect and random effect, chosen based on preliminary tests and the Sobel test to assess mediation effects. The findings reveal that investment decisions and capital structure enhance firm performance, whereas dividend policy reduces performance, and institutional ownership exerts no significant influence. In the firm value model, only capital structure demonstrates a positive and significant effect, while other variables show no direct impact. Mediation analysis confirms that investment decisions and capital structure indirectly strengthen firm value through firm performance, as effective investment allocation and leverage improve productivity and profit, which the market interprets as higher valuation. Conversely, dividend policy and institutional ownership do not exhibit mediating roles.The novelty of this research lies in incorporating institutional ownership into the financial decision firm value framework, thereby extending governance perspectives in corporate finance. Theoretically, the study reinforces firm performance as a key transmission mechanism in corporate finance models, while practically it highlights the importance of performance-oriented strategies and governance-based ownership in sustaining firm value under market uncertainty.